EVALUASI RANSUM MENGANDUNG Indigofera zollingeriana TERHADAP ANAK KAMBING LEPAS SAPIH - Suharlina Suharlina; D.A. Astuti; Nahrowi Nahrowi; A. Jayanegara; L. Abdullah (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
This study was objected to evaluate the nutritional values of ration containing Indigofera zollingeriana to post-weaning goat kids performans. Randomized completely design were used to four types of rations. The 16 heads of ettawah gradebreed post-weaning goad kids (14-21 body weight) were maintained during 8 weeks. I. zollingeriana forage were formulated into R1, R2, R3, and R4 concentrate feeds with proportion 0, 20, 40, and 60% I. zollingeriana, respectively. The rations were I0 (75% R1 + 25% napier grass), I20 (75% R2 + 25% napier grass), I40 (75% R3 + 25% napier grass), I60 (75% R4 + 25% napier grass), respectively. The variables observed were nutrient intake, digestibility, nitrogen utilization, blood nutrients, average daily gain (ADG) and feed efficiency. The data were analyzed using analysis of variance. The result showed that the crude protein (CP) intake of I40 was higher (P<0.05) than I0. The organic matter digestibility value of I20 was higher (P<0.05) than I60. The CP digestibility values of I20 and I40 were higher (P<0.05) than I0 and I60. The total digestible nutrient value of I0 and I20 were higher (P<0.05) than I40 and I60. The nitrogen (N) intake of I0 was less than (P<0.05) I40. The N retention of I40 was higher (P<0.05) than I0 and I60, while I20 was higher (P<0.05) than I0. The net nitrogen utilization of I20 and I40 were higher than I0 and I60. There were no significantly differences on total protein, albumin and immunoglobulin G values of blood serum. The cholesterol serum values of I40 and I60 were less (P<0.05) than I0 and I20. The ADG of I20 was higher (P<0.05) than I0 and I60. The feed efficiency of I20 was highest (P<0.05) than other rations. Key words: dairy goat, Indigofera zollingeriana, nitrogen utilization